2020
DOI: 10.1021/acs.organomet.0c00628
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Scope and Mechanism for Transmetalation of Hydrocarbyl Ligands on Complexes Relevant to C–H Activation

Abstract: We report the transmetalation of hydrocarbyl fragments (Me, Bn, Ph) from a variety of organometallic complexes relevant to C–H activation (Ir, Rh, W, Mo) to Pt­(II) electrophiles. The scope of suitable hydrocarbyl donors is remarkable in that three different classes of organometallics with widely varying reactivity all undergo the same general reaction with Pt­(II) electrophiles. A competitive substituent effect experiment reveals faster transmetalation of more electron-rich hydrocarbyl groups. This study sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…While transmetalation of stoichiometric, preformed organometallic reagents is a key step in cross-coupling reactions (e.g., Zn to Pd in Negishi coupling), selective transmetalation between two catalytic intermediates, each present in low concentrations and each bearing ancillary ligands, is less well understood and can be a barrier to reaction development. Limited studies on transmetalation between two transition metals have been reported, which can be used to inform multimetallic reaction design. This area was reviewed by Casares and Espinet in the context of multimetallic reactions of group 10 metals . Pioneering studies by Osakada and Yamamoto, Puddephatt, , Cross, and others on transmetalation between transition metals, primarily groups 10–12 (Ni, Pd, Pt, Cu, Hg), noted that the metal electronic structure, coordination sphere, and steric hindrance all contributed to an efficient process, suggesting a dinuclear bimetallic intermediate with bridging carbon and X-type ligands was key.…”
Section: Classification Of Multimetallic Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…While transmetalation of stoichiometric, preformed organometallic reagents is a key step in cross-coupling reactions (e.g., Zn to Pd in Negishi coupling), selective transmetalation between two catalytic intermediates, each present in low concentrations and each bearing ancillary ligands, is less well understood and can be a barrier to reaction development. Limited studies on transmetalation between two transition metals have been reported, which can be used to inform multimetallic reaction design. This area was reviewed by Casares and Espinet in the context of multimetallic reactions of group 10 metals . Pioneering studies by Osakada and Yamamoto, Puddephatt, , Cross, and others on transmetalation between transition metals, primarily groups 10–12 (Ni, Pd, Pt, Cu, Hg), noted that the metal electronic structure, coordination sphere, and steric hindrance all contributed to an efficient process, suggesting a dinuclear bimetallic intermediate with bridging carbon and X-type ligands was key.…”
Section: Classification Of Multimetallic Catalysismentioning
confidence: 99%
“…Pioneering studies by Osakada and Yamamoto, Puddephatt, , Cross, and others on transmetalation between transition metals, primarily groups 10–12 (Ni, Pd, Pt, Cu, Hg), noted that the metal electronic structure, coordination sphere, and steric hindrance all contributed to an efficient process, suggesting a dinuclear bimetallic intermediate with bridging carbon and X-type ligands was key. More recently, Lewis has studied transmetalation from a variety of additional transition metals (Ir, Rh, Mo, W) to Pt, showing that a variety of groups could be transferred (−CH 3 , −CH 2 Ar, −Ph) and that steric effects impacted reaction rates; less hindered, lower coordinate complexes reacted faster. ,, Both sets of studies noted that the nature of the organic fragment was also paramount to rate acceleration. While these studies provide general models for transmetalation, understanding is not yet at the level that successful transmetalation between two transition metals can be predicted with certainty.…”
Section: Classification Of Multimetallic Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent low propensity of these complexes to transfer aryl groups (over cyanide and thiolato groups) might also explain why biaryl coupling products were not observed under either stoichiometric or catalytic conditions. This selectivity thus effectively prevents an otherwise possible catalyst decomposition through a cross-electrophile coupling pathway that would lead to biaryl formation and presumably inactive [Ni­(dcype)­X 2 ] complexes. …”
Section: Mechanism Involving Transmetalationmentioning
confidence: 99%
“…The design of more functional group metathesis reactions will benefit from a greater mechanistic understanding, especially given the need to identify a suitable transfer mechanism to exchange two chemically distinct functional groups. Importantly, this understudied transfer of two functional groups between two complexes of the same transition metal, in particular between two nickel complexes, has broad relevance in catalysis, as it might be involved in several other reactions classes, e.g., cross-electrophile couplings, C–H activation or polymerization reactions. Despite numerous reports on transmetalation between two transition-metal centers, , there is only scattered literature on transmetalation between two nickel centers. , These studies were limited to isolated experiments based either on product detection upon mixing of two complexes , or on the kinetic observation of second order in catalyst concentration . Important key questions regarding the transmetalation, most notably whether the aryl groups or the other X-type ligands were exchanged in these reactions, thus remain largely unanswered.…”
Section: Introductionmentioning
confidence: 99%